2022
DOI: 10.1155/2022/7281144
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Cercaricidal Activity of Sida acuta Burm. F. and Sida rhombifolia Linn. (Malvaceae) Hydroethanolic Extracts, Cytotoxicity, and Phytochemical Studies

Abstract: Despite the global efforts, schistosomiasis remains a public health problem in several tropical and subtropical countries. One of the major challenges in the fight against schistosomiasis is the interruption of the parasite life cycle. Here, we evaluated the anticercarial, cytotoxicity, and phytochemical profiles of Sida acuta (HESa) and Sida rhombifolia (HESr) hydroethanolic extracts (Malvaceae). Schistosoma mansoni cercaria was collected from fifteen Biomphalaria pfeifferi-infected snails. Twenty-five cercar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…It has been considered that alkaloids were responsible for the cytotoxic effects as they were approved for their activity against cercariae and miracidia. The present finding is in accordance with that reported by Membe Femoe et al [6] who studied the effect of the plants Sida acuta (HESa) and Sida rhombifolia (HESr) hydroethanolic extracts against Schistosoma mansoni cercariae. They reported that the cercaricidal potential of these ingredients as their phytochemicals belonging to alkaloids might damage the cercariae tegument and disturb its motor activity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It has been considered that alkaloids were responsible for the cytotoxic effects as they were approved for their activity against cercariae and miracidia. The present finding is in accordance with that reported by Membe Femoe et al [6] who studied the effect of the plants Sida acuta (HESa) and Sida rhombifolia (HESr) hydroethanolic extracts against Schistosoma mansoni cercariae. They reported that the cercaricidal potential of these ingredients as their phytochemicals belonging to alkaloids might damage the cercariae tegument and disturb its motor activity.…”
Section: Discussionsupporting
confidence: 94%
“…Coustau and Théron [3] define compatibility as a characteristic of a host-parasite system, where the parasite species have the ability to obtain transmission using the host species and establishing infection. Many investigations were conducted to study the effects of different molluscicides of plant origin at low concentrations on the biological aspects of the snails and the larval stages of S. mansoni [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cercaricidal activity demonstrated by the plants under study could be attributed to their secondary metabolites, such as flavonoids, saponins, and alkaloids [ 58 ]. In previous studies, the total alkaloids, saponins, and essential oils from Nigella sativa [ 59 ], isoflavonoids from Millettia thonningii [ 60 ], and alkaloids from J. elliptica [ 57 ] demonstrated significant cercaricidal activity against S. mansoni cercariae.…”
Section: Discussionmentioning
confidence: 99%
“…It is a tropical weed of pastures, road sides and waste areas [5]. Research has revealed that juice from leaf of Sida acuta has schistosomicidal activity [6] and antihelminthic activity for intestinal worms [4]. The root inhibits embryo implantation or growth in the mice.…”
Section: Introductionmentioning
confidence: 99%